Mothering and ambivalence - Hollway, Wendy; Featherstone, Brid (Routledge, 1997)
Children's rights, lone motherhood and the breakdown of families are all issues at the forefront of current social debate in the West, with little agreement on what constitutes good parenting, or how the needs of both mother and child are best met. The feminist contribution to this debate is particularly important in keeping in view the diverse identities of all those who provide mothering. The psychoanalytic contribution is often undervalued and misunderstood. Mothering and Ambivalence brings together authors from therapeutic, academic and social work backgrounds to discuss depen.